Current and Future Treatments for Persistent Pulmonary Hypertension in the Newborn. Issue 4 (19th July 2018) - Pedersen, Jonas; Hedegaard, Elise R.; Simonsen, Ulf; Krüger, Marcus; Infanger, Manfred; Grimm, Daniela
Abstract: Persistent pulmonary hypertension in newborn (PPHN) is a serious and possibly fatal syndrome characterized by sustained foetal elevation of pulmonary vascular resistance at birth. PPHN may manifest secondary to other conditions as meconium aspiration syndrome, infection and congenital diaphragmatic hernia. This MiniReview provides the reader with an overview of current and future treatment options for patients with PPHN without congenital diaphragmatic hernia. The study is based on systematic searches in the databases PubMed and Cochrane Library and registered studies on Clinicaltrials.gov investigating PPHN. Inhaled nitric oxide (iNO) is well documented for treatment of PPHN, but 30% fail to respond to iNO. Other current treatment options could be sildenafil, milrinone, prostaglandin analogues and bosentan. There are several ongoing trials with sildenafil, but evidence is lacking for the other treatments and/or for the combination with iNO. Currently, there is no evidence for effect in PPHN of other treatments, for example tadalafil, macitentan, ambrisentan, riociguat and selexipag used for pulmonary arterial hypertension in adults. Experimental studies in animal models for PPHN suggest effect of a series of approaches including recombinant human superoxide dismutase, L‐citrulline, Rho‐kinase inhibitors and peroxisome proliferator‐activated receptor‐γ agonists. We conclude that iNO is the most investigated and the only approved pulmonary vasodilator for infants with PPHN. In the iNO non‐responders, sildenafil currently seems to be the best alternative either alone or in combination with iNO. Systematic and larger clinical studies are required for testing the other potential treatments of PPHN.